Group A Beta-Hemolytic Streptococcus-Induced Tic-Like Movement Disorder in an Adult: A Case Report - Ilyas, Usman; Umar, Zaryab; Lin, Dana (Curēus (Palo Alto, CA), 2022)
A tic is a sudden, repeated, quick, and uncontrollable movement of a part of the body. Tic disorders have a multifactorial etiology, including genetic predisposition, autoimmunity, and environmental factors. Movement disorders following streptococcal infection are rare and typically present in the pediatric population. We present a unique case of a 31-year-old female admitted with involuntary movements of the upper extremities of three weeks duration. Her movements start as twitching before progressing to one hand hitting the other or hitting her face. She had a strong urge before giving in to complete the action. However, the movements were partially distractable, with considerable overlap between clinical features of organic and functional tics. After a detailed workup, including a negative magnetic resonance imaging (MRI) of the brain with and without contrast, MRI of the spine, computed tomography of the chest, abdomen, and pelvis for neoplasia, as well as blood work for autoimmunity, infections, and paraneoplastic syndrome, the serology came back strongly positive for antistreptolysin O and antideoxyribonuclease B titers. Additionally, a detailed psychiatric assessment ruled out conversion disorder leading to a diagnosis of streptococcus-induced movement disorder. After a failed inpatient trial of aripiprazole, the plan included initiating deutetrabenazine with close outpatient neurology follow-up after discharge.